Political and scientific support for the establishment of the Veterinary School in Lwów - Dzikowski, Andrzej (Kultura-Społeczeństwo-Edukacja, 2020)
Establishment of the veterinary university in Lwów would not be possible without the political support of Galician authorities, i.a. A. Potocki and S. Zamoyski, Galician and Viennese MPs, and professors A. Biesiadecki, P. Seifmann, H. Kadyi, and J. Szpilman, who performed repeated and uninterrupted activities of both official and unofficial character. Their contribution, postulates, commitment, and work undertaken, had overcame the resistance of central governmental powers. Creation of the Lwów veterinary academic school enabled training not only Polish veterinarians in their mother tongue, but was also an opportunity for students from other Slavic states. The aim of the work is to show the role of political and administrative supporters of the illustrious idea of the Veterinary School, and then lead to its elevation to the Academy.